(untitled) (Journal of Engineering, 2021)
The tremendous benefits of using cellular phones, which began to increase and unprecedented spread worldwide last decade, were accompanied by harmful effects on the environment due to the increase in electromagnetic radiation (EMR) which be emitted from mobile phone towers. This effect on humans, animals, and plants, which is considered a form of environmental pollution, was sensed by developed countries and Environmental protection organizations. These countries have established restrictions and enacted laws to reduce their negative impact on living beings. The field survey included six major hospitals and 38 schools were distributed over the central neighbourhoods in Al-Najaf city. The results showed that power density (PD) measurements for 4 out of 6 hospitals and 27 out of 38 schools were higher than the biological limit (BL) adopted in this article. This limit is considered as an indicator of the onset of a harmful effect on brain and body tissues. The highest value for PD in hospitals was 5.62 mW/m2 recorded in Al-Sadr Teaching Hospital. PD measurements ranged from1.33 from 3.92 mW/m2 in the selected schools where its readings exceeded the BL. When comparing the PD measurements at the selected sites with limits set by the "International Commission on Non-Ionizing Radiation Protection (ICNIRP)" they were less than the recommended limit in those specifications. All values of specific absorption rates (SAR) in W/Kg were below the ICNIRP Guidelines’ limit. However, they were above the biological limit for four hospitals and several of the selected schools.